In vitro induction of odontogenic activity of human dental pulp stem cells by white Portland cement enriched with zirconium oxide and zinc oxide components - Saeed Rahimi; Sadegh Salarinasab; Negin Ghasemi; Reza Rahbarghazi; Shahriar Shahi; Amin Salem milani; Baharak Divband; Paria Davoudi (Tabriz University of Medical Sciences, 2019)
Background. The aim of this in vitro study was to investigate the effect of zinc oxide (ZnO) and zirconium oxide (ZrO2) microparticles (MPs) and nanoparticles (NPs) in combination with white Portland cement (WPC) on odontogenic capacity of human dental pulp stem cells over a period of 21 days. Methods. Synthesized ZnO and ZrO2 particles were characterized using scanning electron microscopy and transmission electron microscopy. The viability of human dental pulp stem cells was measured by a 3-(4,5-dimethylthiazolyl-2-yl)-2,5- diphenyltetrazolium bromide assay at 7-, 14- and 21-day intervals after seeding on WPC disks enriched with ZnO and ZrO2 MPs and NPs. Odontogenic potential of ZnO and ZrO2 particles in combination with WPC was investigated by alkaline phosphatase (ALP) activity and ionized calcium level of supernatant culture media at different time intervals. Data were analyzed using one-way ANOVA and post hoc Tukey tests. Results. All the materials exhibited cell viability over a 21-day period, except for WPC with ZnO NPs on day 7, although it was not statistically significant (P>0.05). The ALP activity and ionized calcium level increased in all the groups compared to the control group (P<0.05). ZnO NPs had superior effect on odontogenic activity and calcium ion release compared to ZnO MPs (P=0.046). There was no significant difference between ZrO2 MPs and NPs in odontogenic activity (P>0.05). Conclusion. WPC enriched with ZnO and ZrO2 increased ALP activity and calcium ion release of human dental pulp stem cells over a period of 21 days in vitro.